Composite domain domain sodium battery positive electrode material and preparation method thereof, positive electrode plate, battery and power utilization device

By introducing composite crystal domain structure and low microstress characteristics into the positive electrode material of sodium ion battery, the problem of structural instability at high potential is solved, and higher energy density and long cycle stability are achieved.

CN119852389AActive Publication Date: 2025-04-18TIANJIN ZHONGDIAN NEW ENERGY RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411892265.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide positive electrode materials are unstable at high potentials, resulting in voltage attenuation and energy density loss.

Method used

A sodium-electrode material with a composite crystal domain structure is used to form a material with low micro-stress characteristics by regulating the sodium content, material components, valence state and doping elements. This material introduces the crystal domain A and the crystal domain B of the layered structure into the crystal structure, and achieves uniform embedding of sodium in the interlayer structure through stepwise sodium supplementation and stepwise calcination processes.

Benefits of technology

It improves the structural stability of the material at high potentials, slows down the attenuation of voltage and capacity, and enhances the long cycle stability and specific capacity retention ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852389A_ABST
    Figure CN119852389A_ABST
Patent Text Reader

Abstract

The invention provides a composite domain sodium battery positive electrode material and a preparation method thereof, a positive electrode plate, a battery and an electric device, the chemical general formula of the composite domain sodium battery positive electrode material is Na1-aNibFecMndXxO2, a is more than 0 and less than or equal to 0.25, b + c + d + x = 1, and X is a metal element with average valence sigma less than or equal to 4; a domain domain A and a domain domain B of a layered structure exist in the crystal structure; the absolute value [epsilon] lt of the micro stress of the crystal structure; and 10%. According to the composite domain-domain sodium battery positive electrode material provided by the invention, higher energy density of the material is ensured by regulating and controlling the sodium content, the material components, the valence state and X element doping, other ions are introduced to provide charge compensation, and the structures and the coupling effect of the domain domain A and the domain domain B are regulated and controlled; stress accumulation and lattice strain caused by non-uniform expansion in a material body structure are reduced, formation and migration barriers of oxygen vacancies in the structure are improved, the stability of lattice oxygen in the material is improved, and voltage attenuation and capacity attenuation are slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a composite crystal domain sodium-ion positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] Sodium-ion batteries are regarded as another secondary battery technology suitable for large-scale commercial applications besides lithium-ion batteries due to their advantages in safety and cost. The layered oxide positive electrode materials in them have attracted much attention due to their high specific capacity, fast sodium-ion diffusion kinetics, simple synthesis and low cost.

[0003] At present, the common sodium layered oxide cathode materials are usually of three types: O3 structure, P2 structure, and P / O mixed structure. Researchers have invested a lot of resources to achieve the reversible extraction / embedding of sodium ions in the interlayer structure. However, when Na + When ions are deeply extracted, the transition metal ions with increased valence enhance the covalency of the transition metal-oxygen bond, making it easier for lattice oxygen to participate in the reaction to provide charge compensation. The lattice oxygen is oxidized and precipitated, resulting in a decrease in the van der Waals force between layers, the collapse of the spacing between alkali metal layers, a decrease in the number of sodium ions that can be inserted and removed, and a decrease in the reversible specific capacity. Moreover, the irreversible precipitation of lattice oxygen further aggravates the irreversible transformation of the structure, resulting in severe voltage attenuation, which is manifested as a loss of energy density during long cycles.

[0004] Therefore, it is urgent to start from the material structure design and improve the structural stability of the material in the high potential deep desodium state by optimizing the material crystal structure, slow down the voltage decay, and improve the long-term energy cycle stability. Summary of the invention

[0005] The purpose of the present invention is to provide a composite crystal domain sodium battery positive electrode material and a preparation method, a positive electrode sheet, a battery and an electrical device to solve the problems existing in the background technology.

[0006] The technical solution of the present invention comprises: a composite crystal domain sodium-based positive electrode material, wherein:

[0007] The chemical formula is Na 1-a Ni b Fe c Mn d X x O 2 , 0<a≤0.25, b+c+d+x=1, X is a metal element with an average valence state σ≤4;

[0008] There are layered domains A and B in the crystal structure.

[0009] The absolute value of the microstress in the crystal structure is ε<10%.

[0010] Furthermore, in the X-ray powder diffraction pattern measured using Cu-Kα rays, the composite crystal domain sodium positive electrode material has at least the following at 2θ of 15° to 18°:

[0011] Corresponding to the diffraction peak M of the (002) crystal plane in the crystal domain A, the diffraction angle of the diffraction peak M is θ M , half peak width is β M ;

[0012] Corresponding to the diffraction peak N of the (003) crystal plane in the crystal domain B, the diffraction angle of the diffraction peak N is θ N , half peak width is β N ;

[0013] Where: 2θ M <2θ N ,

[0014] Furthermore, X is one or more of Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo and W, and 0<x<0.15.

[0015] Furthermore, a≤db,

[0016] Furthermore, there are ordered Ni-O, Fe-O, and Mn-O octahedra in the crystal domain A and the crystal domain B, the Na-O in the crystal domain A is a triangular prism coordination structure, and the Na-O in the crystal domain B is an octahedral coordination structure.

[0017] The technical solution of the present invention also includes: a method for preparing the composite crystal domain sodium positive electrode material as described above, which comprises the steps of:

[0018] Mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0019] sintering the first sintering material at a first temperature to obtain a first calcined product;

[0020] The first calcined product and the type II sodium source are mixed to obtain a second sintered material;

[0021] sintering the second sintering material at a second temperature to obtain a second calcined product;

[0022] crushing and screening the second calcined product to obtain a composite crystal domain sodium positive electrode material;

[0023] Among them, the decomposition temperature or melting temperature of Type I sodium source is lower than that of Type II sodium source, the first temperature is lower than the second temperature, and the median particle size D50 of the composite crystal domain sodium cathode material is 2μm to 12μm.

[0024] Furthermore, the type I sodium source includes NaOH, CH 3 COONa and NaNO 3 At least one of;

[0025] In the first sintering material, the ratio of the molar amount of the sodium element to the total molar amount of the non-sodium metal elements is w1,0 <w1<0.5·(1-a);

[0026] Class II sodium sources include Na 2 CO 3 、NaHCO 3 and Na 2 C 2 O 4 At least one of;

[0027] In the second sintering material, the ratio of the molar amount of sodium element in the type II sodium source to the total molar amount of non-sodium metal elements in the first calcined product is w2,1-a <w1+w2<1.05·(1-a);

[0028] The nickel source, iron source, manganese source and X source respectively include at least one of chloride, acetate, oxalate, carbonate, bicarbonate and nitrate containing the corresponding metal element;

[0029] The first temperature is 500° C., and sintering is performed at the first temperature for 1 to 10 hours;

[0030] The second temperature is 850-1100° C., and sintering is performed at the second temperature for 6-30 hours;

[0031] After sintering, the furnace is cooled. During the cooling process, the relative humidity of the environment is ≤30%;

[0032] During the process of crushing and screening the second calcined product, the relative humidity of the environment is ≤20%.

[0033] The technical solution of the present invention also includes: a positive electrode plate, wherein the positive electrode plate contains the composite crystal domain sodium positive electrode material as described above.

[0034] The technical solution of the present invention also includes: a battery, wherein the battery contains the positive electrode sheet as described above.

[0035] The technical solution of the present invention also includes: an electrical device, wherein the electrical device contains the battery as described above.

[0036] The present invention has the following beneficial effects: the composite crystal domain sodium positive electrode material provided by the present invention ensures that the material has a higher energy density, introduces other ions to provide charge compensation, and regulates the structure and coupling of crystal domain A and crystal domain B, thereby balancing the electrostatic attraction and repulsion between the sodium layer / transition metal layer; the sodium is uniformly embedded in the interlayer structure by step-by-step sodium supplementation and step-by-step calcination, thereby inducing the differentiation of the material microstructure to form two different Na-O coordination structures and materials with an absolute value of microstress of <10%. The low microstress characteristics of the composite crystal domain sodium positive electrode material reduce the stress accumulation and lattice strain caused by the uneven expansion in the bulk structure of the material, improve the interaction between oxygen ions and the transition metal layer, increase the formation and migration barriers of oxygen vacancies in the structure, and synergize with the introduced charge compensation ions to improve the stability of the lattice oxygen in the material and slow down the voltage decay and capacity decay. Thus, the material provided by the present invention has a high energy density of 1.5 MW at high potential (4.2 V vs Na / Na + ) shows stronger long-cycle stability and specific capacity and voltage retention ability. In addition, the material process is simple and easy to scale up for industrial production, reducing product costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM image of the composite crystal domain sodium positive electrode material prepared in Example 1 of the present invention;

[0038] Figure 2 This is the XRD diagram of the composite crystal domain sodium cathode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with embodiments and accompanying drawings:

[0040] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.

[0041] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.

[0042] In the first aspect of the present invention, a composite crystal domain sodium positive electrode material is proposed, which improves the structural stability of the material in the high potential deep de-sodium state by providing additional charge compensation ions and increasing the formation and migration barriers of oxygen vacancies, slows down voltage decay, and improves energy long cycle stability. According to the research on sodium positive electrode materials by the inventors of this technical solution, it is found that not only is the microstress state of the material crystal structure closely related to the oxygen vacancy concentration, but also the coupling effect of microstress and oxygen vacancies has an important influence on the formation energy and migration energy of oxygen vacancies. Reducing the microstress of the material crystal structure can increase the formation and migration barriers of oxygen vacancies in the structure and improve the stability of lattice oxygen; and the microstress of the material crystal structure is closely related to the coupling of crystal domains in the material. Therefore, the inventors of this technical solution adjust the microstress of the material by constructing a sodium positive electrode material with a composite crystal domain, adjusting the material composition, element valence, doping elements, synthesis formula, etc., and adjusting the state of each crystal domain.

[0043] Based on the above research and analysis, the inventors of this technical solution have determined through experiments and exploration that the chemical formula of the composite crystal domain sodium positive electrode material in this embodiment is Na 1-a Ni b Fe c Mn d X x O 2 , 0<a≤0.25, b+c+d+x=1, X is a metal element with an average valence state σ≤4; there are layered domains A and B in the crystal structure of the composite domain sodium positive electrode material, and the domains A and B are coupled to change the microstress of the material crystal structure. The inventors of the present technical solution have found in their research that when the absolute value ε of the microstress of the crystal structure is controlled within 10%, the oxygen vacancy concentration in the material can be effectively reduced, the interaction between oxygen ions and the transition metal layer can be improved, and the formation and migration barriers of oxygen vacancies in the structure can be increased, thereby improving the stability of lattice oxygen, inhibiting voltage decay, and improving the energy retention rate during high cut-off voltage cycles.

[0044] In the above technical scheme, the sodium content is controlled to ensure that the material has a higher energy density, and the structure of crystal domain A and crystal domain B is regulated, thereby regulating the microstress of the crystal structure. Charge compensation is provided by ions of Ni, Fe, Mn, X, etc., to comprehensively improve the structural stability of the material in the high-potential deep desodium state, slow down voltage decay, and improve the long-cycle energy stability.

[0045] In the composite crystal domain sodium positive electrode material that meets the above conditions, there are ordered Ni-O, Fe-O, and Mn-O octahedrons in the crystal domain A and the crystal domain B, and the Na-O in the crystal domain A is a triangular prism coordination structure, and the Na-O in the crystal domain B is an octahedral coordination structure. More sodium ions are released through the Na-O triangular prism coordination structure in the crystal domain A, ensuring that the composite crystal domain sodium positive electrode material has a higher specific capacity, and the Na-O octahedral coordination structure with a large sodium interlayer spacing in the crystal domain B is used to increase the diffusion rate of sodium ions between transition metal layers in the composite crystal domain sodium positive electrode material, reduce the migration barrier of sodium ions, and ensure that the material has high energy density and high charge and discharge efficiency; the existence of ordered Ni-O, Fe-O, and Mn-O octahedrons in the crystal domain A and the crystal domain B can provide a stable skeleton for the material structure, improve the structural stability of the material in the charge and discharge cycle, and improve the structural stability of the material in the high potential deep de-sodium state by adjusting the micro-stress state of the material crystal structure.

[0046] In the further research of the inventors, it was found that coupling of crystal domain A and crystal domain B with different Na-O coordination structures can reduce the microstress of the composite crystal domain sodium positive electrode material and ensure that the sodium ions have a complete and continuous deintercalation channel between the layers; and in the composite crystal domain sodium positive electrode material, the change of material microstress caused by the coupling of crystal domain A and crystal domain B inside the material is closely related to the half-peak width and diffraction angle of the characteristic peak in the powder X-ray diffraction spectrum. The different Na-O coordination environments and distributions in crystal domain A and crystal domain B are manifested as different characteristic peaks in powder X-ray diffraction. In the X-ray powder diffraction spectrum measured using Cu-Kα rays, the composite crystal domain sodium positive electrode material has the following in the range of 2θ=15°~18°: the diffraction peak M corresponding to the (002) crystal plane in crystal domain A, and the diffraction angle of diffraction peak M is θ M , half peak width is β M , and the diffraction peak N corresponding to the (003) crystal plane in the crystal domain B, the diffraction angle of the diffraction peak N is θ N , half peak width is β N , 2θ M <2θ N ; By optimizing the Williamson-Hall equation β hkl ·cosθ=kλ / D+4ε·sinθ,β hkl is the half-peak width of the (hkl) crystal plane in the XRD spectrum, θ is the 1 / 2 diffraction angle, ε is the lattice microscopic strain, and the absolute value of the crystal structure microstress of the composite crystal domain sodium cathode material and the correlation formula of the characteristic peaks of the crystal domain A and the crystal domain B are obtained. Based on this correlation, the magnitude of microstress in the crystal structure of the material can be intuitively determined, and combined with the formation of oxygen vacancies, migration barriers, etc., it can be determined how to adjust the coupling state of crystal domain A and crystal domain B.

[0047] The states of the above-mentioned domain A and domain B are affected by various aspects such as material composition, valence states of various elements, doping elements, and synthesis methods. According to the findings of the inventors in this technical solution during research: the contents of sodium and manganese elements in the material composition determine the number of deintercalatable sodium ions and the content of sodium ion vacancies in the material, and the content of sodium ion vacancies affects the interplanar spacings of the (003) plane and the (002) plane. When 0 < a ≤ 0.25, it can ensure that the material has a relatively high specific capacity and a relatively high diffusion rate of sodium ions between transition metal layers, reducing the migration barrier of sodium ions. When a ≤ d - b, by restricting the number of Na vacancies, on the one hand, it helps to lower the valence state of Ni ions and utilize Ni 2+ / 3+ / 4+ to provide more charge compensation, and on the other hand, it helps to increase the valence state of Mn ions and reduce the content of Mn with a +3 valence, avoiding Mn 3+ from causing lattice distortion and stress accumulation.

[0048] While doping metal elements into the sodium-ion battery cathode material has been partially proven in research to be helpful for improving structural stability, the inventors found in their research that the electronic structure states of element X are quite different from those of Ni, Fe, and Mn. The introduction of such elements will activate the electrochemical activity of some oxygen ions. Especially when the average valence state σ of element X > 4, the element charge number and electron transfer ability are enhanced. After bonding with oxygen, the electrochemical activity of oxygen ions is significantly improved, and it is easy to induce the redox reaction of oxygen ions, resulting in the loss of voltage and energy density. Therefore, to further optimize the electrochemical performance of the composite domain sodium-ion battery cathode material, the inventors of this technical solution conducted in-depth research and found that in the composite domain sodium-ion battery cathode material that meets the above conditions, when the following conditions are met: X is one or more of Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, and W, 0 < x < 0.15, and σ ≤ 4, it can ensure that Ni, Fe, and Mn provide charge compensation as the main stable electrochemical active elements and weaken the redox of oxygen anions.

[0049] In addition, starting from the mutual influence of each component, the inventors comprehensively considered the sodium content, sodium vacancies, the contents and valence states of non-sodium metal elements (Ni, Fe, Mn, X), etc., and designed the composite domain of the material to determine another core technical parameter of this technical solution: The inventors found through a large number of experiments and explorations that when the number of sodium vacancies in the component is relatively low and the content of manganese element is relatively high compared to Ni, Fe, and X, which in turn affects the valence state and distribution of Mn ions and has an adverse effect on the lattice distortion of the structure. When When the number of sodium vacancies in the components is relatively high, the manganese content is relatively low compared to Ni, Fe, and X. The former leads to an increase in the repulsion of the transition metal-oxygen layer, and the latter leads to a decrease in the structural stability of the material, making it difficult to achieve lower material microstress.

[0050] The inventors also found in their research that when the composite crystal domain sodium positive electrode material that meets the above conditions has a median particle size D50 of 2 μm to 12 μm, it helps to ensure the compaction density and electrochemical reaction activity of the material, avoiding the problem of too small particles leading to low compaction density or too large particles leading to difficulty in sodium ion deintercalation; its specific surface area is 0.1 m 2 / g~1.5m 2 / g, it helps to ensure sufficient contact between the material and the electrolyte, so that it has better electrochemical reaction activity; when its water content is less than 500ppm, it helps to reduce the side reaction between trace water in the material and the electrolyte; when its residual sodium carbonate is less than 3.0wt.%, it helps to reduce the decomposition and gas production of sodium carbonate under high voltage, thereby improving the cycle performance of the battery.

[0051] The second aspect of the present invention provides a method for preparing the composite crystal domain sodium positive electrode material described in the first aspect. The preparation method provided in this embodiment comprises the following steps:

[0052] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0053] In this step, the type I sodium source includes NaOH, CH 3 COONa and NaNO 3 At least one of the following: the nickel source, iron source, manganese source, and X source respectively include at least one of chloride, acetate, oxalate, carbonate, bicarbonate, and nitrate containing the corresponding metal element; in the first sintering material, the ratio of the molar amount of the sodium element to the total molar amount of the non-sodium metal elements is w1.

[0054] (2) Sintering the first sintering material at a first temperature to obtain a first calcined product.

[0055] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0056] In this step, the type II sodium source includes Na 2 CO 3 、NaHCO 3 and Na 2 C 2 O 4 At least one of; in the second sintering material, the molar amount of sodium element in the Class II sodium source to the total molar amount of non-sodium metal elements in the first calcined product is w2.

[0057] (4) Sinter the second sintering material at a second temperature to obtain a second calcined product.

[0058] (5) Crush and screen the second calcined product to obtain a composite crystal domain sodium-based cathode material with a median particle size D50 of 2 μm to 12 μm.

[0059] In contrast, type I sodium source has a relatively low decomposition temperature or melting temperature. Therefore, the first temperature should be lower than the second temperature. Preferably, the first temperature is 500 °C, which can achieve the melting of type I sodium source. When 0 < w1 < 0.5·(1 - a), it can effectively promote the insertion of sodium ions into the material matrix at low temperature, improve the uniformity of sodium ion distribution, and ensure that the material has low micro-stress. In the inventor's experimental exploration, it was found that when w1 > 0.5·(1 - a), the excessive type I sodium source is prone to rediffusion during the secondary high-temperature calcination, resulting in segregation of crystal domains in the material structure and increasing the micro-stress of the material.

[0060] Since type II sodium source has a relatively high decomposition temperature or melting temperature, it is preferably to set the second temperature to 850 - 1100 °C to transform type II sodium source into a molten state at high temperature, promote the secondary insertion of sodium ions into the material matrix, slow down the non-uniformity of sodium ion diffusion and distribution, and reduce the structural micro-stress of the material.

[0061] Preferably, the sintering time at the first temperature is controlled within 1 - 10 h, and the sintering time at the second temperature is controlled within 6 - 30 h. After each sintering, it is cooled with the furnace. During the cooling process with the furnace, the relative humidity of the environment ≤ 30%, which helps to reduce the water molecule insertion reaction during the material cooling process, reduce the surface residual alkali and possible structural damage; during the process of crushing and screening the second calcined product, the relative humidity of the environment ≤ 20%, which helps to reduce the moisture and residual sodium carbonate content of the finished material.

[0062] In the third aspect of the present invention, a positive electrode sheet is proposed, which contains the composite crystal domain sodium-based cathode material described in the first aspect.

[0063] In the fourth aspect of the present invention, a battery is proposed, which contains the positive electrode sheet described in the third aspect.

[0064] In the fifth aspect of the present invention, an electrical device is proposed, which contains the battery described in the fourth aspect.

[0065] The present invention will be described in detail below through examples and comparative examples.

[0066] Example 1

[0067] (1) Mix the nickel source, iron source, manganese source, X source and type I sodium source to obtain a first sintering material;

[0068] In this step, the type I sodium source is NaOH, the nickel source is NiO, and the iron source is Fe 2 O 3 , the manganese source is Mn 2 O 3 , X sources are ZnO, CuO and Al 2 O 3 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Cu:Al=0.40:0.2225:0.2225:0.445:0.05:0.03:0.03. After use, they are mixed evenly in a high-speed mixer.

[0069] (2) sintering the first sintering material at a first temperature of 500° C. for 5 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 20%.

[0070] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0071] In this step, the type II sodium source is Na 2 CO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Cu:Al=0.45:0.2225:0.2225:0.445:0.05:0.03:0.03, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0072] (4) sintering the second sintering material at a second temperature of 950° C. for 24 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 20%.

[0073] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 5%, and a chemical formula of Na 0.85 Ni 0.2225 Fe 0.2225 Mn 0.445 Zn 0.05 Cu 0.03 Al 0.03 O 2 Composite crystal domain sodium battery positive electrode material.

[0074] Example 2

[0075] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0076] In this step, the type I sodium source is NaNO 3 , the nickel source is NiO, the iron source is Fe 2 O3 , the manganese source is Mn 2 O 3 , X sources are LiOH, CaO and TiO 2 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Li:Ca:Ti=0.05:0.184:0.184:0.552:0.02:0.01:0.05. After use, they are mixed evenly in a high-speed mixer.

[0077] (2) sintering the first sintering material at a first temperature of 500° C. for 3 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 20%.

[0078] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0079] In this step, the type II sodium source is NaHCO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Li:Ca:Ti=0.80:0.184:0.184:0.552:0.02:0.01:0.05, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0080] (4) sintering the second sintering material at a second temperature of 1000° C. for 6 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 25%.

[0081] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 18%, and a chemical formula of Na 0.83 Ni 0.184 Fe 0.184 Mn 0.552 Li 0.02 Ca 0.01 Ti 0.05 O 2 Composite crystal domain sodium battery positive electrode material.

[0082] Example 3

[0083] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0084] In this step, the type I sodium source is CH 3 COONa, nickel source is Ni(OH) 2 , the iron source is FeCl 3 , the manganese source is MnCO 3 , X source is TiO 2 、Cu(NO3 ) 2 and ZrO 2 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Ti:Cu:Zr=0.35:0.276:0.184:0.46:0.02:0.05:0.01. After use, they are mixed evenly in a high-speed mixer.

[0085] (2) sintering the first sintering material at a first temperature of 500° C. for 3 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 20%.

[0086] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0087] In this step, the type II sodium source is Na 2 C 2 O 4 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Ti:Cu:Zr=0.50:0.276:0.184:0.46:0.02:0.05:0.01, wherein Na refers to sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0088] (4) sintering the second sintering material at a second temperature of 1100° C. for 6 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 20%.

[0089] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 20%, and a chemical formula of Na 0.85 Ni 0.276 Fe 0.184 Mn 0.46 Ti 0.02 Cu 0.05 Zr 0.01 O 2 Composite crystal domain sodium battery positive electrode material.

[0090] Example 4

[0091] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0092] In this step, the type I sodium source is NaOH and NaNO 3 , the nickel source, iron source and manganese source are Ni 0.30 Fe 0.05 Mn 0.65 (OH) 2 , X source is Mg(OH) 2 and Cr2 O 3 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Mg:Cr=0.40:0.267:0.0445:0.5785:0.1:0.01. After taking, mix them evenly in a high-speed mixer.

[0093] (2) sintering the first sintering material at a first temperature of 500° C. for 3 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 28%.

[0094] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0095] In this step, the type II sodium source is NaHCO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Mg:Cr=0.45:0.267:0.0445:0.5785:0.1:0.01, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0096] (4) sintering the second sintering material at a second temperature of 900° C. for 30 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 28%.

[0097] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 20%, and a chemical formula of Na 0.84 Ni 0.267 Fe 0.0445 Mn 0.5785 Mg 0.1 Cr 0.01 O 2 Composite crystal domain sodium battery positive electrode material.

[0098] Example 5

[0099] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0100] In this step, the type I sodium source is NaNO 3 , the nickel source is Ni(CH 3 COO 2 , the iron source is Fe 2 (C 2 O 4 ) 3 , the manganese source is MnCO 3 , X source is Li 2 CO 3 and WO 3, and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Li:W=0.40:0.235:0.235:0.47:0.05:0.01. After use, they are mixed evenly in a high-speed mixer.

[0101] (2) sintering the first sintering material at a first temperature of 500° C. for 3 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 30%.

[0102] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0103] In this step, the type II sodium source is NaHCO 3 and Na 2 CO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Li:W=0.50:0.235:0.235:0.47:0.05:0.01, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0104] (4) sintering the second sintering material at a second temperature of 900° C. for 20 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 30%.

[0105] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 20%, and a chemical formula of Na 0.89 Ni 0.235 Fe 0.235 Mn 0.47 Li 0.05 W 0.01 O 2 Composite crystal domain sodium battery positive electrode material.

[0106] Example 6

[0107] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0108] In this step, the type I sodium source is NaOH, and the nickel source, iron source and manganese source are Ni 0.45 Fe 0.05 Mn 0.50 (OH) 2 , X sources are ZnO and SrCO 3 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Sr=0.30:0.414:0.046:0.46:0.04:0.04. After use, they are mixed evenly in a high-speed mixer.

[0109] (2) sintering the first sintering material at a first temperature of 500° C. for 5 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 20%.

[0110] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0111] In this step, the type II sodium source is Na 2 CO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Sr=0.67:0.414:0.046:0.46:0.04:0.04, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0112] (4) sintering the second sintering material at a second temperature of 930° C. for 20 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 30%.

[0113] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 20%, and a chemical formula of Na 0.97 Ni 0.414 Fe 0.046 Mn 0.46 Zn 0.04 Sr 0.04 O 2 Composite crystal domain sodium battery positive electrode material.

[0114] Example 7

[0115] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0116] In this step, the type I sodium source is NaOH, the nickel source is NiO, and the iron source is Fe 3 O 4 , the manganese source is MnO 2 , X sources are CuO and Nb 2 O 5 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Sr=0.30:0.23625:0.23625:0.4725:0.05:0.005. After use, they are mixed evenly in a high-speed mixer.

[0117] (2) sintering the first sintering material at a first temperature of 500° C. for 5 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 30%.

[0118] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0119] In this step, the type II sodium source is NaHCO 3 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Zn:Sr=0.50:0.23625:0.23625:0.4725:0.05:0.005, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0120] (4) sintering the second sintering material at a second temperature of 960° C. for 20 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 25%.

[0121] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 10%, and a chemical formula of Na 0.8 Ni 0.23625 Fe 0.23625 Mn 0.4725 Cu 0.05 Nb 0.005 O 2 Composite crystal domain sodium battery positive electrode material.

[0122] Example 8

[0123] (1) mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material;

[0124] In this step, the type I sodium source is NaNO 3 , the nickel source is NiO, the iron source is Fe 3 O 4 , the manganese source is MnO 2 , X source is BaCO 3 and MoO 3 , and the elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Ba:Mo=0.30:0.22375:0.04475:0.6265:0.1:0.005. After use, they are mixed evenly in a high-speed mixer.

[0125] (2) sintering the first sintering material at a first temperature of 500° C. for 5 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a first calcined product; the relative humidity of the environment during the cooling process is 20%.

[0126] (3) mixing the first calcined product and the type II sodium source to obtain a second sintered material;

[0127] In this step, the type II sodium source is Na 2 C 2 O4 ; The elements are taken according to the following molar ratio: Na:Ni:Fe:Mn:Ba:Mo=0.45:0.22375:0.04475:0.6265:0.1:0.005, wherein Na refers to the sodium of Class II sodium source, and are mixed evenly by mechanical means after use.

[0128] (4) sintering the second sintering material at a second temperature of 850° C. for 20 hours, and cooling the material to below 100° C. in the furnace after sintering to obtain a second calcined product; the relative humidity of the environment during the cooling process is 25%.

[0129] (5) crushing and screening the second calcined product, wherein the relative humidity of the environment during the crushing and screening process is 10%, and a chemical formula of Na 0.75 Ni 0.22375 Fe 0.04475 Mn 0.6265 Ba 0.1 Mo 0.005 O 2 Composite crystal domain sodium battery positive electrode material.

[0130] Comparative Example 1

[0131] The only difference compared with Example 1 is that in step (1) of Comparative Example 1: the X source is Nb 2 O 5 , and the elements are taken in the following molar ratio: Na:Ni:Fe:Mn:Nb=0.40:0.2225:0.2225:0.445:0.11, and then mixed to obtain the first sintering material; in step (3), the elements are taken in the following molar ratio: Na:Ni:Fe:Mn:Nb=0.45:0.2225:0.2225:0.445:0.11, wherein Na refers to the sodium of Class II sodium source, and then mixed to obtain the second sintering material.

[0132] The final chemical formula is Na 0.85 Ni 0.2225 Fe 0.2225 Mn 0.445 Nb 0.11 O 2 Sodium battery cathode materials.

[0133] Comparative Example 2

[0134] The only difference compared with Example 1 is that in step (1) of Comparative Example 2, no X source is added, and other raw materials are taken according to the following molar ratio of elements: Na:Ni:Fe:Mn=0.40:0.25:0.25:0.50, and then mixed to obtain the first sintering material; in step (3), the following molar ratio of elements are taken: Na:Ni:Fe:Mn=0.45:0.25:0.25:0.50, wherein Na refers to sodium of Class II sodium source, and then mixed to obtain the second sintering material.

[0135] The final chemical formula is Na 0.85 Ni 0.25 Fe 0.25 Mn 0.50 O 2 Sodium battery cathode materials.

[0136] Comparative Example 3

[0137] The only difference compared with Example 1 is that in step (1) of Comparative Example 3, the following elements are taken in a molar ratio: Na:Ni:Fe:Mn:Zn:Cu:Al=0.30:0.2225:0.2225:0.445:0.05:0.03:0.03, and then mixed to obtain the first sintering material.

[0138] The final chemical formula is Na 0.75 Ni 0.2225 Fe 0.2225 Mn 0.445 Zn 0.05 Cu 0.03 Al 0.03 O 2 Sodium battery cathode materials.

[0139] Comparative Example 4

[0140] The only difference compared with Example 1 is that in step (3) of Comparative Example 4, the following elements are taken in a molar ratio: Na:Ni:Fe:Mn:Zn:Cu:Al=0.55:0.2225:0.2225:0.445:0.05:0.03:0.03, wherein Na refers to sodium of Class II sodium source, which is taken and mixed to obtain the second sintering material.

[0141] The final chemical formula is Na 0.95 Ni 0.2225 Fe 0.2225 Mn 0.445 Zn 0.05 Cu 0.03 Al 0.03 O 2 Sodium battery cathode materials.

[0142] Comparative Example 5

[0143] The only difference compared with Example 1 is that in step (1) of Comparative Example 5, no Fe source is added, and other raw materials are taken according to the following molar ratio of elements: Na:Ni:Mn:Zn:Cu:Al=0.40:0.445:0.445:0.05:0.03:0.03, and then mixed to obtain the first sintering material; in step (3), the following molar ratio of elements are taken: Na:Ni:Mn:Zn:Cu:Al=0.60:0.445:0.445:0.05:0.03:0.03, wherein Na refers to sodium of Class II sodium source, and then mixed to obtain the second sintering material.

[0144] The final chemical formula is NaNi 0.445 Mn 0.445 Zn 0.05 Cu 0.03 Al 0.03 O 2 Sodium battery cathode materials.

[0145] Comparative Example 6

[0146] The only difference compared with Example 1 is that in step (1) of Comparative Example 6, other raw materials are not taken according to the following molar ratio of elements: Na:Ni:Fe:Mn:Zn:Cu:Al=0.40:0.2225:0.445:0.2225:0.05:0.03:0.03, and are mixed after taking to obtain the first sintering material; in step (3), the following molar ratio of elements is taken: Na:Ni:Fe:Mn:Zn:Cu:Al=0.45:0.2225:0.445:0.2225:0.05:0.03:0.03, wherein Na refers to sodium of Class II sodium source, and are mixed after taking to obtain the second sintering material.

[0147] The final chemical formula is Na 0.85 Ni 0.2225 Fe 0.445 Mn 0.2225 Zn 0.05 Cu 0.03 Al 0.03 O 2 Sodium battery cathode materials.

[0148] Comparative Example 7

[0149] The only difference compared with Example 1 is that in step (1) of Comparative Example 7, other raw materials are not taken according to the following molar ratio of elements: Na:Ni:Fe:Mn:Zn:Cu:Al=0.40:0.445:0.2225:0.2225:0.05:0.03:0.03, and are mixed after taking to obtain the first sintering material; in step (3), the following molar ratio of elements are taken: Na:Ni:Fe:Mn:Zn:Cu:Al=0.45:0.445:0.2225:0.2225:0.05:0.03:0.03, wherein Na refers to sodium of Class II sodium source, and are mixed after taking to obtain the second sintering material.

[0150] The final chemical formula is Na 0.85 Ni 0.2225 Fe 0.445 Mn 0.2225 Zn 0.05 Cu 0.03 Al 0.03 O 2 Sodium battery cathode materials.

[0151] Comparative Example 8

[0152] The only difference compared with Example 1 is that, in Example 8, the step-by-step mixing operation of Class I sodium source and Class II sodium source is cancelled, and instead: after all the raw materials are taken and mixed at one time according to the ratio in Example 1, the mixture is calcined at 500°C for 5h, then heated to 950°C and calcined for 24h, and then cooled to below 100°C during the furnace cooling process with the relative humidity of the environment being 20%, to obtain a calcined product.

[0153] The chemical formula of the calcined product is Na 0.85 Ni 0.2225 Fe 0.2225 Mn 0.445 Zn 0.05 Cu 0.03 Al 0.03 O 2 .

[0154] The present invention uses the following method to conduct physical and chemical characterization tests on the composite crystal domain sodium cathode materials prepared in Examples 1-8 and the sodium cathode materials prepared in Comparative Examples 1-8 (hereinafter referred to as samples) and obtain corresponding test results.

[0155] (1) The morphology of the composite crystal domain sodium cathode material prepared in Example 1 was observed using a scanning electron microscope (SEM). The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the composite crystal domain sodium cathode material prepared in Example 1 is in the form of regular flaky single crystal particles, with a particle size of about 3 μm to 5 μm.

[0156] (2) ICP test: The sample is dissolved in hydrochloric acid and prepared into a solution of a certain concentration. The content and chemical formula composition of the metal elements in the sample are tested using inductively coupled plasma atomic emission spectrometry. The calculation results are shown in Table 1.

[0157] (3) XPS test: By testing the value and change of photoelectron kinetic energy / binding energy, the elements on the surface of the positive electrode material are analyzed. The obtained data are fitted using Casa XPS software to analyze the chemical valence state of the material. The test and σ calculation results are shown in Table 1.

[0158] Table 1ICP and XPS test results

[0159]

[0160] (4) XRD test: The Cu-Kα target was used, the emission wavelength λ = 0.154 nm, the scanning voltage was 40 kV, the current was 40 mA, the step scanning method was used, the scanning range was 10° to 90°, and the test results were used to calculate the absolute value of the microstress ε of the material. The results are shown in Table 2. Among them, the XRD spectrum of the composite crystal domain sodium positive electrode material prepared in Example 1 is shown in Figure 2 As shown, it has excellent crystallinity, and there are two diffraction peaks in the range of 2θ = 15° to 18°. M and θ N They correspond to the (002) crystal plane of domain A and the (003) crystal plane of domain B respectively.

[0161] Table 2 XRD test results and ε

[0162]

[0163]

[0164] (5) Test method for median particle size D50: The particle size distribution and median particle size D50 of the sample were tested using Malvern laser particle size analyzer Mastersizer 3000. The results are shown in Table 3.

[0165] (6) Specific surface area test method: The specific surface area of ​​the sample was tested by a dynamic method. The sample was placed in a U-shaped tube and a helium-nitrogen mixed gas with a volume ratio of 1:4 was introduced. After the mixed gas flowed through the sample, the adsorption amount of the sample was obtained based on the change in gas concentration before and after adsorption. The results are shown in Table 3.

[0166] (7) Moisture test method: Karl Fischer (coulometric method) is used for testing. The ambient dew point should not be lower than -18°C. The sample is weighed and placed in a sample bottle. The heating tank temperature of the Karl Fischer titrator is then set to 170°C and the carrier gas flow rate is 20 mL / min. After the test, the moisture content is read on the moisture tester. The results are shown in Table 3.

[0167] Table 3 Particle size, specific surface area and moisture test results

[0168]

[0169] (8) Electrochemical performance test

[0170] The specific preparation method of the sodium secondary battery and its positive electrode sheet is as follows: the sample is mixed with acetylene black, carbon nanotubes, and polyvinylidene fluoride in a mass ratio of 90:5:1:4, and an appropriate amount of N-methylpyrrolidone is added as a dispersant, and ground into a slurry; then the slurry is evenly coated on a single side of an aluminum foil, vacuum dried at 120°C for 10 hours, the dried electrode sheet is rolled with a roller machine, and the aluminum foil is cut with a slicer to be cut into a circular electrode sheet with a diameter of 1.3 cm, and the loading amount of the active material is controlled at 10 mg cm -2 About. The half-cell was assembled in an argon atmosphere glove box, with a water partial pressure of ≤0.1ppm and an oxygen partial pressure of ≤0.1ppm. Metallic sodium was used as the counter electrode, 1MNaPF6 (EC / DEC, volume ratio of 1:1) solution was used as the electrolyte, and a button cell of CR2032 type was assembled.

[0171] Sodium ion battery capacity and cycle test method: button cells were charged and discharged at room temperature using constant current charge and discharge mode. First, they were charged to 4.2V (vs. Na / Na) at a current density of 15 mA / g. + ), and then discharged at a constant current density of 15 mA / g to 2.0 V (vs. Na / Na + ) to obtain the gram capacity and first coulombic efficiency of the material. The cycle test was performed at room temperature using a constant current charge and discharge mode for 100 cycles, with a voltage range of 2.0V to 4.1V and a current density of 50mA·g -1 , record the discharge specific capacity (Cap1, Cap100) and discharge specific energy (En1, En100) of the 1st and 100th cycles, then the energy retention rate of 100 cycles is The voltage decays to The results are shown in Table 4.

[0172] Table 4 Electrochemical performance test results

[0173]

[0174]

[0175] As shown in Tables 1 to 4, when the X element in Comparative Example 1 is a high-valence (+5) Nb element and X is not added in Comparative Example 2, although the material has characteristic diffraction peaks M and N similar to the composite crystal domain structure, the microstress of the material is significantly increased, resulting in the deterioration of electrical properties. In Comparative Example 3, the sodium content is reduced, a>db, resulting in the disappearance of the composite crystal domain of the material. In Comparative Example 4, The result is that the material does not have a composite crystal domain, and the residual sodium carbonate content is high, so it does not meet the requirements. In Comparative Example 5, a=db, the material does not have a composite crystal domain, and the residual sodium carbonate content is high, so it does not meet the requirements. In Comparative Examples 6 and 7, a>db and Although there are characteristic diffraction peaks M and N similar to the composite crystal domain structure, the material microstress and residual sodium carbonate content are significantly high, and the electrical properties are deteriorated. In Comparative Example 8, although the same raw materials and proportions as those in Example 1 are used, the gradient sodium supplementation process is not used, and the obtained material has characteristic diffraction peaks M and N similar to the composite crystal domain structure, which is mainly due to the one-time addition of the mixed sodium source, but this is not conducive to the melting and diffusion of the sodium source in the two-step sintering process, making the sodium ion dispersion effect in the material poor, so that the material microstress is high and the electrical properties are poor.

[0176] It can be seen from Table 4 that the first-week coulombic efficiency and energy retention rate after 100 cycles of the composite crystal domain sodium cathode materials prepared in Examples 1-8 are significantly higher than those of the control example, the voltage attenuation is significantly suppressed, and the materials have more excellent electrical properties.

[0177] The composite crystal domain sodium positive electrode material provided by the present invention ensures that the material has a higher energy density, introduces other ions to provide charge compensation, and regulates the structure and coupling of crystal domain A and crystal domain B, thereby balancing the electrostatic attraction and repulsion between the sodium layer / transition metal layer; the uniform embedding of sodium in the interlayer structure is achieved by adopting a step-by-step sodium supplementation and step-by-step calcination method, thereby inducing the differentiation of the material microstructure to form two different Na-O coordination structures and a material with an absolute value of microstress of <10%. The low microstress characteristics of the composite crystal domain sodium positive electrode material reduce the stress accumulation and lattice strain caused by the uneven expansion in the bulk structure of the material, improve the interaction between oxygen ions and the transition metal layer, and increase the formation and migration barriers of oxygen vacancies in the structure. It synergizes with the introduced charge compensation ions to improve the stability of the lattice oxygen in the material and slow down the voltage decay and capacity decay. Therefore, the material provided by the present invention has a low microstress characteristic at high potential (4.2Vvs.Na / Na + ) shows stronger long-cycle stability and specific capacity and voltage retention ability. In addition, the material process is simple and easy to scale up for industrial production, reducing product costs.

[0178] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A composite crystal domain sodium positive electrode material, characterized in that: The composite crystal domain sodium positive electrode material: The chemical formula is Na 1-a Ni b Fe c Mn d X x O2, 0<a≤0.25, b+c+d+x=1, X is a metal element with an average valence state σ≤4; There are layered domains A and B in the crystal structure. The absolute value of the microstress in the crystal structure is ε<10%.

2. The composite crystal domain sodium positive electrode material according to claim 1, characterized in that: In the X-ray powder diffraction spectrum measured using Cu-Kα rays, the composite crystal domain sodium positive electrode material has at least the following at 2θ of 15° to 18°: Corresponding to the diffraction peak M of the (002) crystal plane in the crystal domain A, the diffraction angle of the diffraction peak M is θ M , half peak width is β M ; Corresponding to the diffraction peak N of the (003) crystal plane in the crystal domain B, the diffraction angle of the diffraction peak N is θ N , half peak width is β N ; Where: 2θ M <2θ N , 3. The composite crystal domain sodium positive electrode material according to claim 1 or 2, characterized in that: X is one or more of Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo and W, and 0<x<0.

15.

4. The composite crystal domain sodium positive electrode material according to claim 3, characterized in that: a≤d-b, 5. The composite crystal domain sodium positive electrode material according to any one of claims 1-2 and 4, characterized in that: There are ordered Ni-O, Fe-O, and Mn-O octahedra in the crystal domain A and the crystal domain B. The Na-O in the crystal domain A is a triangular prism coordination structure, and the Na-O in the crystal domain B is an octahedral coordination structure.

6. A method for preparing the composite crystal domain sodium positive electrode material according to any one of claims 1 to 5, characterized in that: Includes steps: Mixing a nickel source, an iron source, a manganese source, an X source and a type I sodium source to obtain a first sintering material; sintering the first sintering material at a first temperature to obtain a first calcined product; The first calcined product and the type II sodium source are mixed to obtain a second sintered material; sintering the second sintering material at a second temperature to obtain a second calcined product; crushing and screening the second calcined product to obtain a composite crystal domain sodium positive electrode material; Among them, the decomposition temperature or melting temperature of Type I sodium source is lower than that of Type II sodium source, the first temperature is lower than the second temperature, and the median particle size D50 of the composite crystal domain sodium cathode material is 2μm to 12μm.

7. The method for preparing a composite crystal domain sodium positive electrode material according to claim 6, characterized in that: Class I sodium sources include at least one of NaOH, CH3COONa and NaNO3; In the first sintering material, the ratio of the molar amount of the sodium element to the total molar amount of the non-sodium metal elements is w1,0 <w1<0.5·(1-a); Class II sodium sources include at least one of Na2CO3, NaHCO3 and Na2C2O4; In the second sintering material, the ratio of the molar amount of sodium element in the type II sodium source to the total molar amount of non-sodium metal elements in the first calcined product is w2,1-a <w1+w2<1.05·(1-a); The nickel source, iron source, manganese source and X source respectively include at least one of chloride, acetate, oxalate, carbonate, bicarbonate and nitrate containing the corresponding metal element; The first temperature is 500° C., and sintering is performed at the first temperature for 1 to 10 hours; The second temperature is 850-1100° C., and sintering is performed at the second temperature for 6-30 hours; After sintering, the furnace is cooled. During the cooling process, the relative humidity of the environment is ≤30%; During the process of crushing and screening the second calcined product, the relative humidity of the environment is ≤20%.

8. A positive electrode sheet, characterized in that: The positive electrode plate contains the composite crystal domain sodium positive electrode material described in any one of claims 1-5.

9. A battery, characterized in that The battery contains the positive electrode sheet according to claim 8.

10. An electrical device, characterized in that: The electrical device contains the battery according to claim 9.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115295787A

  • Nickel-rich layered oxide material and preparation method and application thereof

    CN115832281A

  • Positive electrode sodium supplementing additive and sodium ion battery

    CN116683025A

  • Positive electrode active material and preparation method and application thereof

    CN116873988A

  • Active material, nonaqueous electrolyte battery, battery pack, and vehicle

    EP3220453A1